Europejskie pogranicza Hiszpanii w oczach polskich podróżników, dyplomatów i żołnierzy (XVI-XIX w.) = The European borderland of Spain in the eyes of Polish travelers (16th - 19th c.) - Kucharski, Adam (Zielona Góra: Lubuskie Towarzystwo Naukowe)
For more than four centuries (16th - 19th) Spain was the target of numerous and remote journeys undertaken by Poles. The Polish accounts of these voyages include many observations concerning Spanish borderlands. Initially, in the 16th and 18th centuries, Spain was perceived by Poles as the borderland of the Christian World protecting Europe from the Muslim invasion as well the door to the New World.
Keywords: podróż; podróżnicy; Hiszpania; Polska; 16-19 w.